Penerapan Dakwaan Oleh Penuntut Umum Kejaksaan Negeri Padang Terhadap Pelaku Tindak Pidana Perjudian Online Di Kota Padang - Andre; Diana Arma; Nilma Suryani (Delicti : Jurnal Hukum Pidana Dan Kriminologi, 2023)
There are online gambling cases where the Public Prosecutor tends to charge with alternative charges using Article 303 of the Criminal Code while the court facts and evidence explain clearly about online gambling. It is interesting to study the implementation of charges by the Public Prosecutor against perpetrators of online gambling crimes in Padang City and the reasons why the Public Prosecutor charges online gambling cases with Article 303 of the Criminal Code, whereas Article 27 paragraph 2 of the ITE Law also specifically regulates online gambling. This paper uses empirical juridical research methods, where the data used is primary data and secondary data through literature study. The application of charges in online gambling cases by the Public Prosecutor needs to pay attention to several things, the most important of which is to complete the elements relating to Article 27 paragraph 2 of Law No. 19 of 2016 concerning Amendments to Law No. 11 of 2008 concerning ITE. In many online gambling cases that go to the Padang District Prosecutor's Office, there are deficiencies in evidence to complete the elements in the ITE so that the gambling articles in the Criminal Code are used